PGC-related gene variants and elite endurance athletic status in a Chinese cohort: A functional study - He, Z.-H.; Hu, Y.; Li, Y.-C.; Gong, L.-J.; Cieszczyk, P.; Maciejewska-Karlowska, A.; Leonska-Duniec, A.; Muniesa, C. A.; Marin-Peiro, M.; Santiago, C.; Garatachea, N.; Eynon, N.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study aims to examine the association between proliferator-activated receptor ? (PGC)-gene family-related single nucleotide polymorphisms (SNPs) and elite endurance runners' status in a Chinese cohort, and to gain insights into the functionality of a subset of SNPs. Genotype distributions of 133 SNPs in PPARGC1A, PPARGC1B, PPRC1, TFAM, TFB1M, TFB2M, NRF1, GABPA, GABPB1, ERRa, and SIRT1 genes were compared between 235 elite Chinese (Han) endurance runners (127 women) and 504 healthy non-athletic controls (237 women). Luciferase gene reporter activity was determined in 20 SNPs. After adjusting for multiple comparisons (in which threshold P-value was set at 0.00041), no significant differences were found in allele/genotype frequencies between athletes and controls (when both sexes were analyzed either together or separately). The lowest P-value was found in PPARGC1A rs4697425 (P = 0.001 for the comparison of allele frequencies between elite female endurance runners and their gender-matched controls). However, no association (all P > 0.05) was observed for this SNP in a replication cohort from Poland (194 endurance athletes and 190 controls). Using functional genomics tool, the following SNPs were found to have functional significance: PPARGC1A rs6821591, rs12650562, rs12374310, rs4697425, rs13113110, and rs4452416; PPARGC1B rs251466 and rs17110586; and PPRC1 rs17114388 (all P < 0.001). This study found no significant association between PGC-related SNPs and elite endurance athlete status in the Chinese population, despite some SNPs showing potential functional significance and the strong biological rationale to hypothesize that this gene pathway is a candidate to influence endurance exercise capacity.